Feeling at Home in Two Cultural Worlds: Bicultural Identity Integration Moderates Felt Authenticity. (February 2022) - Mok, Aurelia
Bicultural individuals navigate and identify with two cultures. Biculturals differ in levels of Bicultural Identity Integration (BII)—how much their two cultural identities are combined and compatible (high BII) versus divided and conflicting (low BII). We hypothesized that during conformity in cultural ingroup contexts, biculturals with low BII feel inauthentic (being untrue to themselves), whereas biculturals with high BII feel authentic (being true to themselves). Across four experiments with Asian-Americans, expressing cultural conformity (vs. non-conformity) in Asian or American contexts produced felt inauthenticity among participants with low BII but not high BII (Studies 1–3). Felt inauthenticity was due to cultural identity threat (perceived identity exclusion) (Study 2). Activating self-kindness counteracted felt inauthenticity for low BII participants during cultural conformity (Study 3) and produced felt authenticity (Study 4). Our findings imply that responding kindly to the self makes biculturals at ease in their cultural homes, at least temporarily.